Discovery of a broad-spectrum monoclonal antibody recognizing a conserved, linear epitope WFYDGYPT on VP1 protein of Enterovirus A species - Lie Fu; Wei-Ping Jin; Wen-Hui Wang; Chen Wang; Sha-Sha Qian; Meng-Jun Wang; Rui-Lun Liu; Song-Zhuang Li; Ya-Xin Du; Sheng-Li Meng; Jing Guo; Ze-Jun Wang; et al. (Virology Journal)
Abstract Background The hand, foot and mouth disease (HFMD) was caused by species of Enterovirus A and Enterovirus B in the Asian-Pacific region. Broad-spectrum monoclonal antibodies (mAb) that can bind multiple serotypes of enteroviruses have gradually become a research hotspot in the diagnosis, prevention and treatment of HFMD. Methods In this study, a mAb 1H4 was obtained using monoclonal antibody technology by immunizing purified virus particles of Coxsackievirus A5 (CV-A5). Examined by indirect immunofluorescence and Western blotting, 1H4 detected successfully all seven selected serotypes CV-A2, CV-A4, CV-A5, CV-A6, CV-A10, CV-A16 and EV-A71 of Enterovirus A and targeted structural protein VP1. Results The mAb 1H4 showed no cross-reactivity to strains of Enterovirus B and Enterovirus C. A linear epitope 202WFYDGYPT209 was identified as the minimal binding region of 1H4 by indirect ELISAs with overlapped and truncated peptides of VP1. Alanine scanning test found that W202, F203, D205, G206, Y207, P208, and T209 were key residues in the epitope region. BLAST of the epitope in the NCBI genus Enterovirus protein database indicates that the epitope sequence is highly conserved among Enterovirus A species, but not among the other Enterovirus species. Conclusions The results suggest that the mAb 1H4 may be a useful tool for development with a cost-effective and accurate method for surveillance and early differentiation of serotypes from Enterovirus A species to other species.